Peran Theory of Reasoned Action Terhadap MinatT Menggunakan Produk Bagi Hasil Bank Syariah - Kayati Kayati (UNSIKA (Universitas Singaperbangsa Karawang), 2018)
This research is entitled “The Role of Theory of Reasoned Action to Use Sharing System Product of Syaria Bank”. It is aimed to investigate and analyze the subjective norm, and people’s attitude on the intention to use Sharing System Product of Syaria Bank. This research uses primary data taken from questionnaires distributed to two hundred people from five districts of Cirebon by using purposive sampling method, in which the sample is taken based on the size of the area. In addition, the method of analysis applies is Multiple Regression Analysis. Based on the analysis, it can be concluded that attitude does not affect people’s intention to use sharing system product of Syaria bank, while subjective norm influence the intention to usesharing system product of syaria bank.Keywords: Theory of Reasoned Action, Syaria Bank, sharing system product